Chemical control of Lolium multiflorum: effect of biotype and time of spraying - Pereira, Liese de Vargas; Carvalho, Leonardo Bianco de; Dal Magro, Taísa (Revista de Ciências Agroveterinárias, 2017)
Different herbicides were tested to control two biotypes of Lolium multiflorum, an important weed of annual and perennial crops, applied onto 3-4-leaf and pre-flowering stages. Regardless of stage and biotype, the highest efficacy (>85%) was obtained with paraquat and paraquat+diuron. Any of the tested herbicides promote effective control (>85%) of L. multiflorum when applied to 3-4-leaf plants. When applied in pre-flowering, in addition to paraquat and paraquat+diuron, only glyphosate and iodosulfuron can promote effective control (>85%), but with dependence the biotype. The herbicides paraquat and paraquat+diuron are the most recommended for the control of L. multiflorum.